The ratio bias phenomenon: fact or artifact? - Mathieu Lefèbvre; Ferdinand M. Vieider; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2009)
The ratio bias - according to which individuals prefer to bet on probabilities expressed as a ratio of large numbers to normatively equivalent or superior probabilities expressed as a ratio of small numbers - has recently gained momentum, with researchers especially in health economics emphasizing the policy importance of the phenomenon. Although the bias has been replicated several times, some doubts remain about its economic significance. Our two experiments show that the bias disappears once order effects are excluded, and once salient and dominant incentives are provided. This holds true for both choice and valuation tasks. Also, adding context to the decision problem does not change this outcome. No ratio bias could be found in between-subject tests either, which leads us to the conclusion that the policy relevance of the phenomenon is doubtful at best.
Keywords: C91; D03; D81; I19; 330; Ratio bias; financial incentives; error rates; experiment; Entscheidung bei Unsicherheit; Maßzahl; Bias; Ökonomischer Anreiz; Prospect Theory; Test